Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Transmart Setiabudi Semarang - Nuruddin Mahmud (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2021)
In a situation of increasingly fierce business competition, companies must have a way to be able to win market competition where the main factor is to create satisfaction in the hearts of customers. Transmart Setiabudi Semarang is one of the retailers in the city of Semarang that not only regulates basic needs, but also plays with family. During July-December 2019 the percentage of complaints has increased. The purpose of this study was to see the effect of price, product quality and service quality on customer satisfaction at Transmart Setiabudi Semarang. Data obtained from 100 respondents using purposive sampling technique. This study can be concluded that the variables of price, product quality and service quality have a positive and significant effect on customer satisfaction.